Local atractivity in zip bifurcation (2010)
In this paper we study the local attractiveness of the equilibrium segment that is formed in the phenomenon of the zip fork for a three-dimensional system of nonlinear differential equations. This work can be considered as a generalization of a Farkas result in a fork of zip of competing models.